Ancestral origins and invasion pathways in a globally invasive bird correlate with climate and influences from bird trade. Issue 16 (3rd August 2015) - Jackson, Hazel; Strubbe, Diederik; Tollington, Simon; Prys‐Jones, Robert; Matthysen, Erik; Groombridge, Jim J.
Abstract Invasive species present a major threat to global biodiversity. Understanding genetic patterns and evolutionary processes that reinforce successful establishment is paramount for elucidating mechanisms underlying biological invasions. Among birds, the ring‐necked parakeet (Psittacula krameri) is one of the most successful invasive species, established in over 35 countries. However, little is known about the evolutionary genetic origins of this species and what population genetic signatures tell us about patterns of invasion. We reveal the ancestral origins of populations across the invasive range and explore the potential influence of climate and propagule pressure from the pet trade on observed genetic patterns. Ring‐necked parakeet samples representing the ancestral native range (n = 96) were collected from museum specimens, and modern samples from the invasive range (n = 855) were gathered from across Europe, Mauritius and Seychelles, and sequenced for two mitochondrial DNA markers comprising 868 bp of cytochrome b and control region, and genotyped at 10 microsatellite loci. Invasive populations comprise birds that originate predominantly from Pakistan and northern areas of India. Haplotypes associated with more northerly distribution limits in the ancestral native range were more prevalent in invasive populations in Europe, and the predominance of Asian haplotypes in Europe is consistent with the higher number of Asian birds transported by the pet trade outside the native range. Successful establishment of invasive species is likely to be underpinned by a combination of environmental and anthropogenic influences.